Deirdre, a Tragic Heroine in William Butler Yeats' Deirdre and in J. M. Synge's Deirdre of the Sorrows - Selby, Kamila (Univerzita Pardubice, 2012)
The main purpose of this paper is to provide an analysis of the plays Deirdre of the Sorrows by John Millington Synge and Deirdre by William Butler Yeats which date back to the period of Irish Literary Revival and portray a tragic heroine of Irish mythology, Deirdre. In the initial part of the paper the Irish Literary Revival is contextualized and its main goals are introduced. The original myth and the specificities of the plays are further described. The second part considers analysis of the plays with special attention being paid to the main character of Deirdre. Certain aspects of both plays are then compared.
Deirdre, tragická hrdinka v díle Williama Butlera Yeatse Deirdre a J. M. Synge Deirdre of the Sorrows
Keywords: Deirdre; Deirdre bolestná; Synge, John Millington; Yeats, William Butler; irské národní obrození; irská mytologie; Deirdre of the Sorrows; irish Literary Revival; irish mythology